1996
DOI: 10.1097/00003246-199611000-00006
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of simplified omeprazole suspension for the prophylaxis of stress-related mucosal damage

Abstract: Simplified omeprazole suspension prevented clinically significant upper gastrointestinal bleeding and maintained gastric pH of > 5.5 in mechanically ventilated critical care patients without producing toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
2
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(70 citation statements)
references
References 45 publications
3
64
2
1
Order By: Relevance
“…128 Limited studies of proton pump inhibitors (PPIs) as bleeding prophylaxis have demonstrated their effectiveness in maintaining elevated intragastric pH. [131][132][133] Two trials found no significant bleeding in PPI-treated patients on mechanical ventilation, 131,132 but study size may have precluded detection of significant bleeding. H 2 blockers have been proven to be effective and PPIs are almost certainly effective as well.…”
Section: Gastrointestinal Bleedingmentioning
confidence: 99%
“…128 Limited studies of proton pump inhibitors (PPIs) as bleeding prophylaxis have demonstrated their effectiveness in maintaining elevated intragastric pH. [131][132][133] Two trials found no significant bleeding in PPI-treated patients on mechanical ventilation, 131,132 but study size may have precluded detection of significant bleeding. H 2 blockers have been proven to be effective and PPIs are almost certainly effective as well.…”
Section: Gastrointestinal Bleedingmentioning
confidence: 99%
“…No patient developed clinically significant upper GI bleeding while receiving omeprazole and the mean gastric pH increased significantly, from 3.5 (SD 1.9) before omeprazole administration to 6.8 (SD 0.6) after omeprazole administration. 11 N asogastric administration of 'simplified omeprazole suspension' has also been compared with continuous IV infusion of ranitidine in a randomised study. The study involved 58 patients with the same risk factors as those in the previous study.…”
Section: Alternative Methods Of Omeprazole Administrationmentioning
confidence: 99%
“…Limited data exist on its clinical efficacy; however, available data indicate that proton-pump inhibitors can be efficacious [182][183][184][185][186]. In two prospective series of patients receiving omeprazole oral suspension [182,183], with sizes of 75 and 60 patients, respectively, clinically significant gastrointestinal bleeding was not experienced. In a randomised trial with 67 patients, a greater rate of clinically important bleeding (31 versus 6%, p,0.05), and a trend to a greater rate of VAP patients (14 versus 3%) was found in the patients given ranitidine intravenously versus omeprazole orally [184].…”
Section: Stress Ulcer Prophylaxismentioning
confidence: 99%